Eleocharis atropurpurea (Retz.) J. Presl & C. Presl (Cyperaceae) - A New Record for Andaman & Nicobar Islands and a Note on its Identity - Chandore, A. N.; Kamble, M. Y.; Gosavi, K. V. C. (Journal of the Bombay Natural History Society (JBNHS), 2015)
No Abstract.